A retrospective review of complicated foreign bodies of upper aerodigestive tract - Mahajan, Ritesh; V., Prashanth (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Inhalation/aspiration of foreign bodies (FB) into upper aerodigestive tract are very commonly encountered by otorhinolaryngologists. Most foreign bodies in adults are manageable, but sometimes can lead to fatal consequences in children. However, despite significant advances in instrumentation, they remain a therapeutic and diagnostic challenge. The aim was to study the clinical presentation, site of impaction, complications and management of foreign bodies in upper aerodigestive tract. Methods: A retrospective study was conducted in department of ENT-Head and Neck Surgery, Rajarajeswari Medical College and Hospital, Bangalore. A total of 50 eligible patients were reviewed who got operated for foreign body in upper aerodigestive tract under general anaesthesia. Results: History of foreign body was present in 86% of cases and 25% of the patients had complaints of difficulty in breathing. Nose being most common site in 74%, 70% of the patient belongs to 0-10 age group and male: female ratio was 1.7:1. Complications were seen in 12% of patients. Foreign body removal rate was 100%. Conclusions: Early diagnosis is the key to successful and uncomplicated management of FB in upper aerodigestive tract. An orderly and systematic approach along with proper history and clinical examination is keystone in diagnosis and early management.